2018
DOI: 10.1136/bmjopen-2017-017240
|View full text |Cite
|
Sign up to set email alerts
|

Systematic bias between blinded independent central review and local assessment: literature review and analyses of 76 phase III randomised controlled trials in 45 688 patients with advanced solid tumour

Abstract: ObjectiveUnbiased assessment of tumour response is crucial in randomised controlled trials (RCTs). Blinded independent central review is usually used as a supplemental or monitor to local assessment but is costly. The aim of this study is to investigate whether systematic bias existed in RCTs by comparing the treatment effects of efficacy endpoints between central and local assessments.DesignLiterature review, pooling analysis and correlation analysis.Data sourcesPubMed, from 1 January 2010 to 30 June 2017.Eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 119 publications
2
14
0
Order By: Relevance
“…Similarly, independent clinicians could perform blinded central evaluation of tumour assessment endpoints, but this might have major cost implications 78. In a recent review of randomised controlled trials in solid tumours, there was no systematic bias between the findings from blinded independent central review and local assessment, but there were statistical inconsistencies between the two sets of results in almost a quarter of trials 79. Moreover, previous meta-epidemiological reviews across different therapeutic areas have found that studies with non-blinded assessors of subjective outcomes generate biased findings 4980.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, independent clinicians could perform blinded central evaluation of tumour assessment endpoints, but this might have major cost implications 78. In a recent review of randomised controlled trials in solid tumours, there was no systematic bias between the findings from blinded independent central review and local assessment, but there were statistical inconsistencies between the two sets of results in almost a quarter of trials 79. Moreover, previous meta-epidemiological reviews across different therapeutic areas have found that studies with non-blinded assessors of subjective outcomes generate biased findings 4980.…”
Section: Discussionmentioning
confidence: 99%
“…In a large meta-analysis conducted over 76 phase 3 trials on a total of more than 45 000 patients with solid tumors, Zhang et al 31 calculated the statistical inconsistencies between the end points assessed by locals investigators vs the assessments by independent reviewers; a statistically inconsistent inference was defined as a condition whereby the treatment effect from one of the assessments shows a significant difference, while showing no significant difference from the other assessment. These authors found no significant differences in the treatment effects of ORR between blinded independent central review and local investigators (odds ratio, 1.02; 95%CI, 0.97-1.07), and similar findings were obtained with PFSs.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found no significant differences in the treatment effects of ORR between blinded independent central review and local investigators (odds ratio, 1.02; 95%CI, 0.97-1.07), and similar findings were obtained with PFSs. 31 However, when these authors carried out a direct comparison of response rates between central and local assessments (data obtained from 28 phase 3 trials on solid tumors), they found significantly lower ORR values associated with blinded independent central review assessment compared to those of local investigators, for both experimental (odds ratio, 0.81; 95%CI, 0.76-0.87) and control arms (odds ratio, 0.79; 95%CI, 0.72-0.85). 32 Taken collectively, our data and those of Zhang et al 32 would suggest that the ORRs assessed by local investigators are significantly higher by about 20% compared to those assessed by blinded reviewers, regardless of whether the ORR assessment was carried out in phase 2 or in phase 3 trials.…”
Section: Discussionmentioning
confidence: 99%
“…Independent reviews are conducted primarily to discern and minimise bias that may be introduced by the investigators (28). As such, blinded independent reviews are recommended for clinical trials studying tumour response or disease progression (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%